2020
DOI: 10.3390/bios10100146
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanorods for LSPR Biosensing: Synthesis, Coating by Silica, and Bioanalytical Applications

Abstract: Nanoparticles made of coinage metals are well known to display unique optical properties stemming from the localized surface plasmon resonance (LSPR) phenomenon, allowing their use as transducers in various biosensing configurations. While most of the reports initially dealt with spherical gold nanoparticles owing to their ease of synthesis, the interest in gold nanorods (AuNR) as plasmonic biosensors is rising steadily. These anisotropic nanoparticles exhibit, on top of the LSPR band in the blue range common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 213 publications
(418 reference statements)
1
56
0
1
Order By: Relevance
“…5 Moreover, the position of l-LSPR band displays a higher sensitivity to the variation of the local dielectric environment compared to the LSPR band of spherical nanoparticles, making AuNRs of particular interest for the development of LSPR biosensors. [6][7][8][9] The extensive development of synthesis protocols enables the preparation of particles with desired and controlled properties, mainly using cetyltrimethylammonium bromide (CTAB) as surfactant, surface stabilizer, and shape inducing agent. 10 However, the cytotoxicity of CTAB and its interferences with biological processes, restrict the biomedical applications of AuNRs.…”
Section: Introductionmentioning
confidence: 99%
“…5 Moreover, the position of l-LSPR band displays a higher sensitivity to the variation of the local dielectric environment compared to the LSPR band of spherical nanoparticles, making AuNRs of particular interest for the development of LSPR biosensors. [6][7][8][9] The extensive development of synthesis protocols enables the preparation of particles with desired and controlled properties, mainly using cetyltrimethylammonium bromide (CTAB) as surfactant, surface stabilizer, and shape inducing agent. 10 However, the cytotoxicity of CTAB and its interferences with biological processes, restrict the biomedical applications of AuNRs.…”
Section: Introductionmentioning
confidence: 99%
“…Complementary, Roejarek Kanjanawarut et al 52 reported that DLS measurements can provide information about minor degree of AuNR assembly aggregation than UV-vis spectroscopy. Thus, the slight variation on the translational motion peak that we have observed for AuNRs suggests MB may promote some end-to-end AuNR aggregation 51,52 , however not enough to change the LSPR of the AuNRs observed in the UV-vis extinction spectra (Figure 2). The end-to-end aggregation of AuNRs could be ascribed to interactions of MB (positively charge) with the tips (transverse) of the AuNR surfaces, which are less CTAB coated 52 .…”
Section: Aunr Colloid Dynamic Light Scatteringmentioning
confidence: 81%
“…For the DLS measurements applied to nanorods, in general, the diffusion motions of the nanorods in the colloid play an important role in the intensity of the observed peaks 49,50 . The DLS does not give direct information about the dimension of the nanorods, however, it provides information about modifications around nanorod surface and medium 51 . In general, peaks with lower intensity are ascribed to rotational diffusion motion and peaks with higher intensity to longitudinal diffusion motion 49 .…”
Section: Aunr Colloid Dynamic Light Scatteringmentioning
confidence: 99%
“…By modifying this procedure, it is possible to modify the morphology of NPs. This is commonly the case for the synthesis of gold nanorods, where a surfactant, commonly cetyltrimethylammonium bromide (CTAB), is used to allow the AuNPs to take on a rod-like shape (Amina and Guo, 2020[ 7 ]; Dumur et al, 2020[ 33 ]; Pellas et al, 2020[ 91 ]). Other chemical methods include the Turkevich method, the Brust method and digestive ripening (Amina and Guo, 2020[ 7 ]).…”
Section: Gold Nanoparticlesmentioning
confidence: 99%